Towards general purpose service robots: World Robot Summit – Partner Robot Challenge. (17th September 2022) - Contreras, Luis; Yamamoto, Takashi; Matsusaka, Yosuke; Okada, Hiroyuki
Abstract : Although the skills required to solve specific robotics problems are reaching amazing performances recently, we propose the evaluation of such individual solutions in fully integrated robot systems tested in real daily situations like those presented at international robotics competitions. The World Robot Summit (WRS)– Partner Robot Challenge surges from the necessity to standardise and spread the research on Domestic Service Robots where a series of solutions can be tested to solve a general purpose task in a standard domestic environment. We propose the Tidy-Up task as a benchmark and present the key features behind this challenge as well as our main findings through the several stages in the design process. This approach has been proven successful in different international competitions, namely, the RoboCup Japan Open, the Mexican Tournament of Robotics, the RoboCup Worldwide and the WRS. GRAPHICAL ABSTRACT: UF0001